Evaluation of Kansas Beef Consumers’ Awareness and Understanding of Business-to-Consumer Marketing - L. K. Decker; K. R. Lybarger; J. Kwon; G. Ibendahl; Y. Teng-Vaughan; D. Kehler; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:The objective of the study was to determine the understanding and knowledge level of consumers purchasing beef in a business-to-consumer (B2C) format within Kansas. Study Description:A digital survey was created to evaluate consumers’ familiarity and satisfaction of buying beef in a B2C format. The survey was made available for a two-week period to consumers utilizing the Shop Kansas Farms online social media group. Results:Results of the survey showed 93% of consumers (n = 174) reported having previously purchased beef products from a local producer or locker. Of these, 63.1% reported that their most recent purchase was their first time purchasing in a B2C format and the same percentage of consumers had been purchasing beef in a B2C format for less than five years. The most common methods of purchasing beef in a B2C format were “portion cuts” (24.5%), followed by “quarter beef” (17.0%) and “half beef” (15.1%), or a combination of at least two of these methods (20.7%). Only 5.7% of consumers experienced challenges while purchasing beef in a B2C format, yet 100% of those consumers still intended to continue purchasing beef in this format. When consumers were given options that would be useful to prevent future complaints, the most selected response was “improved consumer knowledge.” The consumers (n = 82) who rated this response as “very effective” or “extremely effective” indicated that “increased state extension resources” would be at least “moderately effective” (82.9%). This indicates that increased state extension resources would be an effective way to improve consumer knowledge. The Bottom Line:Consumers within the state of Kansas are interested in and have positive experiences with purchasing beef in the B2C format. Moreover, most consumers are new consumers to buying beef in the B2C format, indicating that there is increasing demand for beef available for purchase in this format. Results of this study support this but show room for growth within consumer understanding of purchasing beef in a B2C format. Results of this study shows the opportunity for improvement of extension and other resources for consumers.
Keywords: beef; consumer; B2C; business to consumer; meat; marketing